Determination of a Suitable Renewable Energy Source for Mini-Grid Business: A Risk-Based Multicriteria Approach - Ighravwe, Desmond Eseoghene; Babatunde, Moses Olubayo (Journal of Renewable Energy, 2018)
The mini-grid proliferation has helped to improve the current state of electricity supply in several rural areas in developing countries. This is due to the innovations in renewable energy technologies. The impact of this development is the establishment of mini-grid business. There is a need for mini-grid business owners to identify the most suitable energy source for a particular area. To achieve this, proper analysis of risks that impact mini-grid business operations is required for optimal energy source selection. The current study addresses this problem by proposing a conceptual framework that considered risk factors. The conceptual framework analysed scenarios where expected risk values are specified and not specified by decision-makers. This was achieved using fuzzy axiomatic design (FAD), intuitionistic entropy method, and TOPSIS (Technique for Order Performance by Similarity to Ideal Solution) methods. The TOPSIS and FAD results were combined using WASPAS (weighted aggregated sum product assessment) method. The proposed conceptual framework was applied in sub-Sahara Africa, Lagos, Nigeria. During the application of the proposed framework, five renewable energy sources and thirteen types of risks were considered. Information from four decision-makers was used to demonstrate the applicability of the framework. The results obtained showed that unpredictable electricity demand and construction completion risks were identified as the least and most important risks for the selection of renewable energy sources for mini-grid, respectively. The FAD and TOPSIS methods identified wind and biomass energy as the best-ranked energy source for mini-grid business, respectively. The WASPAS method and the FAD results were the same.